Staff of Agro-Industrial Formations and Peculiarities of its Formation and Use - Поліщук, В. С.; Стрильбіцький, П. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The article emphasizes the importance of the preservation and development of labour of staff as a basis for socio-economic development of the AІF. Attention is applies to the need for a flexible response system to ensure the staff AІF and an integrated system approach to the needs of staffing of their manufacturing sector. The study of peculiarities of formation of the personnel of the AІF. The most effective factors that directly affect productivity. Attention is drawn to a method of planning the needs of personnel in the AІF. Stresses the importance of the final accounting of working hours of employees. Indicates the need to monitor the level of implementation of labour standards and improvement of conditions of production and its organization. Attention is applies to the classification of the staff of AІF depending on the specifics of their economic and production activities.